Beneficial effects and safety of traditional Chinese medicine for chronic inflammatory demyelinating polyradiculoneuropathy: A case report and literature review - Xie, Yao; Li, Lesang; Xie, Le; Jiang, Junlin; Yao, Ting; Mao, Guo; Wang, Shiliang; Lin, Anchao; Ge, Jinwen; Wu, Dahua (Frontiers in Neurology, 2023)
Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is an immune-mediated neuropathy. First-line treatments for CIDP include corticosteroids, intravenous immunoglobulin, and plasma exchange. However, the application is always limited by high costs, effectiveness, and adverse events. This study investigated a new potentially effective and safe therapeutic treatment to alleviate CIDP symptoms and improve the quality of life. In the present case, a 47-year-old rural woman presented with weakness and numbness of progressive extremities. She was diagnosed with CIDP based on abnormal cerebrospinal fluid and electromyography. The patient was treated with intravenous dexamethasone for 1 week and with Huangqi-Guizhi-Wuwu and Bu-Yang-Huan-Wu decoctions for 90 days. Surprisingly, after the treatment, the weakness and numbness were eliminated, and the quality of life improved. The varying INCAT, MRC, and BI scores also reflected the treatment effects. After 8 months of discharge, the symptoms did not relapse during the follow-up. We also searched “traditional Chinese medicine (TCM)” and “CIDP” in PubMed, EMBASE, the Web of Science, the Cochrane Library, the Chinese National Knowledge Infrastructure Databases, Wanfang Data, and the Chongqing Chinese Science and Technology Periodical Database. Finally, only ten studies were included in the literature review. Three studies were randomized controlled trials, and seven were case reports or case series. There were 419 CIDP patients, but all study sites were in China. Nine TCM formulas involving 44 herbs were reported, with Huang Qi (Astragalus membranaceus) being the most important herb. In conclusion, the case and literature demonstrated that TCM treatment might be a more effective, low-cost, and safe option for treating CIDP. Although these preliminary findings are promising, a larger sample size and higher-quality randomized clinical trials are urgently required to confirm our findings.